Evaluasi Kebijakan Layanan Kenaikan Pangkat Berbasis Siasn di Badan Kepegawaian Daerah Kabupaten Sidoarjo - Dzuu Washfi Azhmi; Nihayatus Sholichah; Dandy Patria (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The State Civil Apparatus Information System (SIASN) is a digital platform developed by the State Civil Service Agency (BKD) to manage ASN personnel data and information in Indonesia. This study aims to evaluate the SIASN-based promotion service policy at the Sidoarjo Regency Regional Civil Service Agency based on State Civil Service Agency Regulation Number 7 of 2023. The research method used is qualitative research with data collection techniques through in-depth interviews, participatory observation, and documentation studies. Data analysis uses the Miles and Huberman interactive model, while the evaluation framework uses William Dunn's evaluation criteria which include effectiveness, efficiency, adequacy, responsiveness, and accuracy. The evaluation results show that the SIASN-based promotion service policy at the Sidoarjo Regency BKD has been quite effective in achieving the goal of improving service quality and has a good level of efficiency in reducing bureaucratic flows. However, in terms of adequacy, there are still gaps related to human resources and system integration. The policy's responsiveness to ASN needs is quite good although there is still room for improvement in aspects of communication and data updating. The main obstacles identified include weak validity of personnel data, the absence of a bridging system between SIPEKAT and SIASN, limited human resources, and minimal awareness of ASN in updating independent data.